Industry genius : inventions and people protecting the climate and fragile ozone layer - Andersen, Stephen O. (Greenleaf Pub., 2003)
This book presents the inventive genius behind technological breakthroughs by ten global companies including Alcoa, DaimlerChrysler, Honda, ST Micro and Visteon. Readers will gain understanding and insight into how cutting-edge technology is helping protect the climate and/or the ozone layer, while contributing to the company's bottom line. Each chapter chronicles the challenge and triumph of invention, introduces the engineers and executives who overcome conventional wisdom, and demonstrates the contribution these companies are making to environmental protection. In full colour and crammed with graphics to illustrate the creative process of technological breakthroughs, the book is accessible and informative. The genius of these ten companies will inspire the engineer, the policy-maker, the student, the environmentalist, the CEO and the investor alike.